Settlement of Bad Debts Through Non-Litigation Channels to Improve Community Economic Enterprises in Pasuruan - Mar'atul Jadida Fitri; Aryani Witasari (UNISSULA Semarang, 2025)
This study discusses the non-litigation approach to resolving bad debts at PT. BPRS Daya Artha Mentari and its contribution to improving the economy of the Pasuruan community. The study employed a juridical-sociological approach, with data collection techniques including observation, interviews, documentation, and literature review. The results indicate that resolving bad debts through rescheduling, reconditioning, and restructuring is considered more effective, faster, and cheaper than litigation. Non-litigation resolving has a positive impact on improving the economy of the Pasuruan community, particularly for MSMEs, agriculture, industry, and fisheries businesses.